65 Out-of-hospital cardiac arrests in the older population in ireland. (28th September 2016) - Tanner, R; Jensen, M; Masterson, S; Wright, P; Hennelly, D; Andrew, P; Bury, G; O'Donnell, C; O'Reilly, M; Deasy, C
Abstract : Background: Out of hospital cardiac arrest (OHCA) is associated with a poor survival. Age influences survival but it is unclear to what extent. Patient selection is crucial in deciding who should receive attempted resuscitation to optimise outcomes and minimise inappropriate end-of-life management. Aim: To describe the demographics, characteristics and outcomes following resuscitation attempts in OHCA patients aged 70 years and older in the Republic of Ireland. Methods: Data was extracted from the national Out of Hospital Cardiac Arrest Register (OHCAR) for patients aged 70 years and older. Patient and event characteristics were compared across three age categories (70–79; 80–89; 90 years and older). Logistic regression was used to determine the predictors of the primary outcome in the overall cohort (discharge from hospital alive). Results: A total of 2, 443 OHCAs in patients aged 70 years and older were attended by emergency medical services and had resuscitation attempted between 2012 and 2014 in the Republic of Ireland. For the entire cohort, survival to hospital discharge was 3.4%. Asystole was the first rhythm identified in 52.6% of all cases. A shockable initial rhythm persisted as a predictor of survival as age progressed; overall 14.6% of those aged over 70 years survived if the presenting rhythm was shockable, 0.1% of OHCAs survived if asystole was the initial rhythm analysed. Of those suffering an OHCA in a residential institution, 2.2% survived to hospital discharge. Logistic regression analysis showed that an initial shockable initial rhythm and having a witnessed cardiac arrest were independent predictors associated with increased odds of survival to discharge. Conclusion: Resuscitation is a purposeful exercise in those with advancing age when favourable prognostic markers are present. Data on age related survival can inform those discussing end of life decisions.